PERENCANAAN SETTING PENGAMAN SALURAN UDARA TEGANGAN TINGGI 150 KV DENGAN DIBANGUNNYA GIS TANAH LOT - Anak Agung Ngurah Wanda Ariesta; I Gede Dyana Arjana; Tjok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2018)
In an effort to increase electricity supply PT PLN (Persero) build GIS Tanah Lot in Nyitdah Village Tabanan regency. The new GIS development makes the network transmission system High Voltage Air Line 150 kV changed. Changes in this transmission system impact on the channel safety settings due to changes in transmission length and impedance value. Prior to the analysis of the impedance setting, the Distance Relay Distance Zone with current, working time and OCR Relay coordination (Over Current Relay) firstly analyzes short circuit flows two phases and three symmetric phases using ETAP PowerStation program. After calculation of distance relation setting, the value of channel impedance in Tanah Lot GIS is 2,4 + j 6,96 ? with Zone 1 setting (80%): 0,200 + j 0,588 ?, Zone 2 (120%): 0,30 + j 0.882 ?, and Zone 3 (220%): 0.68 + j 2.30 ?. OCR (Over Current Relay) release time setting is indicated by releasing delay (tD>) for Tanah Lot GIS - Antosari and Tanah Lot GIS - The vessel has a value of 0.48 with an actual working time release of 1.134 seconds.